2017
DOI: 10.1177/1010428317698341
|View full text |Cite
|
Sign up to set email alerts
|

A multi-target protein of hTERTR-FAM96A presents significant anticancer potent in the treatment of hepatocellular carcinoma

Abstract: The abilities to escape apoptosis induced by anticancer drugs are an essential factor of carcinogenesis and a hallmark of resistance to cancer therapy. In this study, we identified hTERTR-FAM96A (human telomerase reverse transcriptasefamily with sequence similarity 96 member A) as a new efficient agent for apoptosome-activating and anti-tumor protein and investigated the potential tumor suppressor function in hepatocellular carcinoma. The hTERTR-FAM96A fusion protein was constructed by genetic engineering and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…TERT , located at 5p15.33, which is a susceptibility region of lung cancer, was reported to be connected with pancreatic cancer risk . Human TERT ( hTERT ), an essential component of telomerase, was reported to be expressed in more than 80% of HCC cells . Some researchers suggested that hTERT expression and telomerase activity could serve as useful diagnostic markers in various malignancies .…”
Section: Introductionmentioning
confidence: 99%
“…TERT , located at 5p15.33, which is a susceptibility region of lung cancer, was reported to be connected with pancreatic cancer risk . Human TERT ( hTERT ), an essential component of telomerase, was reported to be expressed in more than 80% of HCC cells . Some researchers suggested that hTERT expression and telomerase activity could serve as useful diagnostic markers in various malignancies .…”
Section: Introductionmentioning
confidence: 99%
“…In collaboration with CIAO1, FAM96A matures ACO1 and stabilizes IREB2, thus connecting cytosolic iron-sulfur protein maturation with cellular iron regulation [29]. It has been shown that FAM96A increases cytotoxic T lymphocyte responses, interferon-γ release, and T lymphocyte infiltration [30]. Studies have shown that FAM96A is a novel pro-apoptotic tumor suppressor that is lost during tumorigenesis.…”
Section: Post-reovirus the Expression Of Vegfb And Fam96a Results In ...mentioning
confidence: 99%
“…FAM96A and FAM96B participate in regulating tumor cell apoptosis by interacting with different proteins [ 47 ]. Some studies have shown that FAM96A can act as a tumor suppressor gene in various human cancers, including liver cancer [ 48 ]. But there is currently no detailed research report on the functional role of FAM96B in tumor progression at present.…”
Section: Discussionmentioning
confidence: 99%